Virtual Store of Personalized Sale for Footwear in the SME sector - Condor Quispe, Luis Enrique (2024)
The footwear industry around the world presents a remarkable dig- ital transformation so as not to lose competitiveness in the market, more and more people are immersed in the purchase of footwear vir- tually. The study focused on designing a new shopping experience through footwear customization, which provided new practices. Having a qualitative-analytical method, where a survey was de- veloped, finding customer satisfaction results, as well as the agile method of application software oriented in business design for footwear, where an e-commerce store called "CustShoes" was devel- oped that allows the user to experience the purchase of personalized shoes in real time making changes such as: size, colors, material, text, etc. In this way the customer can buy a customized product that arrives at home satisfying their needs.